SISTEM PENUNJANG KEPUTUSAN PEMILIHAN ONLINE SHOP DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Mega Primandari Rimba Berlian; Abdul Rahman Kadafi (LPPM Universitas Bina Sarana Informatika, 2021)
Online Shop is one of the mediums of communication as well as electronic commerce (e-commerce). Many factors influence consumer decisions. The number of online shops in the application sometimes makes prospective customers feel worried when choosing an online shop that suits their wishes and consumers will look for reviews on the internet or ask their friends. The purpose of this study is to research which online shop applications are most in demand by the public. With this research, this research applies Decision Support System with Analytical Hierarchy Process (AHP) method in choosing online shop application. The result of the calculation in the study is the role of the highest value which is the result needed as a consideration material by the user to determine the selection of online shop applications. In this online shop application selection research can be concluded that the most popular online shop application is Shopee with the value obtained through the calculation of 0.48 or 48%, Lazada with 19%, then there is Tokopedia 17%, then there is Blibli with 9% gain, and lastly there is Bukalapak with 7% gain.